Methodological discussion of the income measure in the European social survey round 1 - Hoffmeyer-Zlotnik, Jürgen H. P. (Metodološki zvezki, 2006)
During the last decade, the number of cross-national and cross-cultural empirical research has increased; at the same time the need for comparative survey data grew considerably. Also more and more politicians and policy decision makers are looking across the national and cultural borders of their countries. Looking at the question of total net household income, we discus advantages and weaknesses of an input harmonized social survey. We demonstratethe impact of the national social, economic and legal particularities on the answering behavior of the surveyed respondent by comparing across countries the interview outcomes from the European Social Survey (ESS) and the European Community Household Panel (ECHP). ESS used a crude measurement of the total net household income interviewing only one randomly selected household member. ECHP surveyed all persons living in a sampled household and asked all income sources and components of the respondents and the household. In this paper we use ECHP as a reference showing the most accurate method to measure income, and compare this with the interview results of ESS. For comparative social surveys we propose a set of questions on income that takes into account the national circumstances. We get comparable data across countries reflecting the national tax systems, the particular practices in the earning structures and the national habits in summing up the different income components. We expect that such a new fieldwork instrument integrated into the data production of cross-national surveys may increase the analytical power of the comparative socio-demographic variable "total net household income".
Keywords: Measurement; Merjenje; Dohodek; Income; Comparative research; Primerjalne raziskave; družboslovno raziskovanje; primerjalno raziskovanje